Menilai Kualitas Pemimpin: Fit and Proper Test dalam Demokrasi Berbasis Moralitas, Intelektualitas, dan Elektabilitas - Munazih, Muflih (PAMALI: Pattimura Magister Law Review, 2024)
Introduction: The Fit and Proper Test (FPT) is an important process in assessing potential leaders in the democratic country of Indonesia, which aims to ensure that candidates meet the requirements of morality, intellectuality and electability. Based on Law no. 17 of 2014 and Law no. 8 of 2015, the morality aspect requires prospective leaders to have integrity and a good track record. However, challenges arise from politicization which often ignores these values.Purposes of the Research:  The aim of this research is to analyze the effectiveness of the Fit and Proper Test in the context of morality, intellectuality and electability, as well as provide recommendations for improving the leader selection process in Indonesia.Methods of the Research: This research uses a qualitative approach with descriptive analysis, collecting data through literature studies and expert interviews. The results are expected to provide an overview of the effectiveness of the fit and proper test regarding morality, intellectuality and electability, as well as recommendations for future improvements. Historical and conceptual approaches are also applied to systematically understand legal philosophy.Results of the Research: The conclusion of this research confirms that the Fit and Proper Test (FPT) has a vital role in selecting quality leaders in Indonesia. This process must consider morality, intellectuality and electability in accordance with the provisions of the law. Although challenges in implementation often arise due to politicization, transparent and accountable FPT reform is very important to produce leaders who are able to advance the nation.